Polyamide nanofiltration membrane with highly uniform sub-nanometre pores for sub-1 Å precision separation - Liang, Yuanzhe; Zhu, Yuzhang; Liu, Cheng; Lee, Kueir-Rarn; Hung, Wei-Song; Wang, Zhenyi; Li, Youyong; Elimelech, Menachem; Jin, Jian; Lin, Shihong (Nature communications, 2020)
Separating molecules or ions with sub-Angstrom scale precision is important but technically challenging. Achieving such a precise separation using membranes requires Angstrom scale pores with a high level of pore size uniformity. Herein, we demonstrate that precise solute-solute separation can be achieved using polyamide membranes formed via surfactant-assembly regulated interfacial polymerization (SARIP). The dynamic, self-assembled network of surfactants facilitates faster and more homogeneous diffusion of amine monomers across the water/hexane interface during interfacial polymerization, thereby forming a polyamide active layer with more uniform sub-nanometre pores compared to those formed via conventional interfacial polymerization. The polyamide membrane formed by SARIP exhibits highly size-dependent sieving of solutes, yielding a step-wise transition from low rejection to near-perfect rejection over a solute size range smaller than half Angstrom. SARIP represents an approach for the scalable fabrication of ultra-selective membranes with uniform nanopores for precise separation of ions and small solutes. Separating molecules or ions with sub-Angstrom scale precision is important but technically challenging. Here, the authors demonstrate that precise solute-solute separation can be achieved using polyamide membranes formed via surfactant-assembly regulated interfacial polymerization.